Analisis Kebijakan Pemerintah dalam Mengatasi Masalah Pengagguran di Indonesia Pasca Pandemi Covid-19 - Lestari, Dwi Siti (CV. Civiliza Publishing, 2023)
Introduction/Main Objectives: This research aims to find government policies for unemployment in Indonesia after Covid 19. Research Methods: The method used in this research is to wait for a qualitative approach with a research library. Finding/Results: The research results show that the government has implemented policies to address the unemployment problem in post-Covid-19 Indonesia, as follows; (1) Allocating funds for handling Covid-19. (2) Organizing income tax incentive programs and relaxing credit payments. (3) Provision of social assistance to 70.5 million informal sector workers who are included in the vulnerable and poor categories. (4) Conduct various competency and productivity based trainings. (5) Expanding job opportunities for workers affected by the pandemic. (6) Opening of consultation, information and complaint services for workers related to Occupational Safety and Health. (7) Issuance of Pre-Employment Cards to develop competency and job opportunities. Conclusion: The government has carried out the right policies to address the problem of unemployment in Indonesia after Covid-19